Moorean Sentences in Update Semantics - Sedlár, Igor (Organon F, 2011)
We outline a novel solution to Moore’s paradox within the framework of update semantics, which explains Moorean absurdity in terms of non-cohesiveness. It is argued that, unlike the outlined solution, Gillies’ treatment of the paradox within this framework is not satisfactory.